Visual damage at flexural response milestones for blast-resistant precast concrete panels with varying reinforcement. (15th June 2019) - Gombeda, Matthew J.; Naito, Clay J.; Quiel, Spencer E.
Highlights: Precast concrete panels with different reinforcement indices were examined. Panels were designed for similar nominal capacities but varying net tensile strain. Experimental results show dependency of visual damage on net tensile strain. A parametric study shows the effect of varying reinforcement on blast limit states. P-I curves were used to compare enhanced and conventional blast design methods. Abstract: Current blast design practices correlate the flexural performance of reinforced concrete façade panels to empirically developed component response milestones. These milestones were correlated with observed progressions of visual damage from experimental tests. Selection of these performance metrics is based on the component classification and construction type but are not sensitive to variations in cross-section design parameters. This study examines the flexural performance of singly-reinforced solid precast concrete panels (i.e. single wythe, non-insulated) with varying reinforcement indices to evaluate the correlation of mechanical response with the progression of visual damage. Experimental tests are performed using a set of panels designed to similar flexural strengths and the results show that visually graded damage at each flexural milestone is not reliably consistent with visual damage guidelines from previously published design standards. Rather, the experimental results show that the progression of visual damage and component plasticity are dependent on net tensile strain and reinforcement index. The results of experimental testing are used as the basis for a parametric study which highlights the deviations in performance from current state of practice approaches when incorporating realistic material response of the panels.